Click, shop, slay: analyzing the influence of digital marketing on youth's fashion brands in Malaysia - Hassan, Mohammad Mujaheed; Haris Fadzilah, Asmaul Husna; Roger, Jessie Paige; Ismail, Mohammad Naim; Chan, Tak Jie; Abu Bakar, Nur Fardilla; Ramdzan Ali, Al Amirul Eimer (Kuram ve uygulamada eğitim yönetimi, 2024)
Anticipated growth in internet usage among Malaysians is projected to reach 1.9 million users, reflecting a 5.68 percent increase between 2023 and 2028. This trend underscores the strategic importance for businesses to establish a presence on social networking sites to leverage digital marketing for effective brand promotion. Despite evidence supporting the efficacy of digital marketing, certain fashion brands remain hesitant to adopt this approach. This research aims to examine the influence of digital marketing channels on the purchasing decisions of youths in Malaysia, focusing on fashion brands. The study seeks to elucidate the relationship between email marketing, online advertising, social media marketing, and mobile marketing on the purchasing behavior of Malaysian youth. Employing a quantitative methodology, an online questionnaire administered via Google Form was utilized, with 374 undergraduate students from a public university in Malaysia participating. Data analysis involved Statistical Package for the Social Sciences (SPSS), Pearson Correlation Coefficient, and Multiple Linear Regression analysis. The findings indicate positive and significant relationships between online advertising, social media marketing, and mobile marketing with youths' purchase decisions concerning fashion brands. However, email marketing did not demonstrate a significant positive relationship. This study underscores the importance for fashion brand owners to leverage digital platforms effectively and highlights the specific digital channels that exert the most influence on youth purchasing behavior.